Infraspecific morphological variations of Salvia limbata in Iran - Talebi, S.M.; Yadegari, P.; Behzadpour, S.; Matsyura, A. V. (Acta Biologica Sibirica, 2019)
Salvia limbata is an aromatic herb of Lamiaceae, which distributed in different parts of Iran. Studies have revealed that this species has several benefit compounds for human health. In this study, we investigated infra‒specific morphological difference in this species. In total, 21 inflorescence morphological features were evaluated in eight populations; ten individuals were evaluated per each population. Data were analysed using SPSS and MVSP softwares. Morphological traits highly differed among the studied populations and ANOVA test revealed significant differences among most of them. According to UPGMA tree, PCA and PCO plots of morphological characteristics, we reported four distinct phenotypes among the studied populations. CA. Joined plot revealed each of these group were characterized by special traits, which were useful in identification of them. Two phenotypes were monotypic, while the rest were composed of two to four populations. This species has a relative large geographical distribution, the distribution of its populations in diverse area will prevent the focus of natural selection in a given direct. Therefore different phenotypes were found in its different populations.